Psychological wellbeing of lower-limb amputees in two Nigerian Teaching Hospitals: the role of psychological and demographic factors (2012)
The role of psychological (personality/actors and depression) and demographic factors (age, gender, average monthly income, and marital status) on the psychological wellbeing (PWB) of amputees was investigated. The cross-sectional study included 96 male and 16 female purposively selected below-knee amputees (age Ẋ =36.25) attending post operative clinics in two Nigerian Teaching Hospitals. Regression, correlational analysis and t-tests revealed a significant inverse relationship between PWB and openness to experience (r=-.295, p<.05), conscientiousness (r=249, p<.05) and agreeableness (r=-.278. p<.05). A significant inverse relationship was also observed between depression and conscientiousness (r=-.359, p<.05). Demographic factors jointly predicted PWB (R2 =.24, F (3. 156) = 2.35: P<.05). Further overage monthly income (β= .302, p<0.01), and age (β =.193. P < 0.001) significantly independently predicted PWB, while marital status (β =.085. P>0.05), and gender (β=-.104, P>0.05) did not. There is a significant inverse relationship between age and overage monthly income (r=-.264, p<.05), while a significant positive relationship was recorded between average monthly income and PWB (r=.186. p<.01). There was no significant relationship between age and PWB (r=.026, p>.05). This shows the importance of psychological and socio-demographic factors in psychological adjustment to amputation. Efforts aimed at improving income, reducing depression, and stabilising the personality of amputees will be helpful in reducing the psychological stress associated with lower-limb amputation.